1991
DOI: 10.2307/3869300
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Maize Sucrose Phosphate Synthase in Tomato Alters Leaf Carbohydrate Partitioning

Abstract: We isolated a complementary DNA sequence for the enzyme sucrose phosphate synthase (SPS) from maize utilizing a limited amino acid sequence. The 3509-bp cDNA encodes a 1068-amino acid polypeptide. The identity of the cDNA was confirmed by the ability of the cloned sequence to direct sucrose phosphate synthesis in Escherichia coli. Because no plant-specific factors were necessary for enrymatic activity, we can conclude that SPS enzyme activity is conferred by a single gene product. Sequence comparisons showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
1
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 8 publications
3
62
1
1
Order By: Relevance
“…These variations might be due to differences in culture conditions. Yet, a decrease in starch content, paralleled by an increase in sucrose, has also been observed in transgenic tomato plants expressing higher levels of SPS (Worrell et al, 1991), indicating the importance of SPS activity in C partitioning. This finding is relevant to our system, as an increase in SPS activation state was found only for mycorrhiza formation, not for increased CO # .…”
Section: Carbohydrate Metabolism In Shootsmentioning
confidence: 99%
“…These variations might be due to differences in culture conditions. Yet, a decrease in starch content, paralleled by an increase in sucrose, has also been observed in transgenic tomato plants expressing higher levels of SPS (Worrell et al, 1991), indicating the importance of SPS activity in C partitioning. This finding is relevant to our system, as an increase in SPS activation state was found only for mycorrhiza formation, not for increased CO # .…”
Section: Carbohydrate Metabolism In Shootsmentioning
confidence: 99%
“…In C 3 -plants, PEPC acts to replenish TCA cycle intermediates which serve as source material for the synthesis of amino acids (Stitt 1999). On the other hand, C distribution to sucrose increases with rising SPS levels (Worrel et al 1991, Signora et al 1998, Murchie et al 1999. Galtier et al (1993) demonstrated a positive relationship between SPS activity and the sucrose/starch ratio by changing the level of SPS in tomato transformed with a maize SPS gene, resulting in increased starch degradation in the chloroplasts.…”
Section: Introductionmentioning
confidence: 99%
“…This fact may provide an explanation for the perturbations in carbon metabolism observed in these plants (Worrell et al, 1991). For example, increased activities of SPS were shown to modify assimilate partitioning in the leaf (Worrell et al, 1991). We have studied the metabolic and physiological effects of the expression of the maize gene in the next generation of tomato plants (the TI generation, grown from seed).…”
mentioning
confidence: 99%
“…It has been shown that the generation of one type of subunit (molecular mass 135 kD) is sufficient to assemble the SPS holoenzyme in Escherichia coli (Worrell et al, 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation